Alaska's Katmai, Lake Clark & Alagnak : [videorecording (DVD)] bears & fish (Discoveries-- America. National parks., 2012)
Features footage of Alaska's Katmai National Park & Preserve, Lake Clark National Park & Preserve, sockeye salmon in teh Brooks River ecosystem, and fly-fishing for all 5 species of salmon, rainbow trout, char and grayling in the Alagnak Wild River.